Metodologia para guiar o desenvolvimento e implementação industrial de novas tecnologias unindo engenharia econômica e Engenharia de (bio)processos e sistemas : aplicação à produção de etanol de segunda geração - Furlan, Felipe Fernando (2016)
Lignocellulosic ethanol, also called second generation ethanol, is a promising alternative for decreasing fossil fuel dependency globally. Nevertheless, its production process still needs further improvements in order to achieve industrial feasibility. Despite the massive experimental effort in this area, threshold values to be pursued in order to attain an economically feasible process are still missing. In this context, this study focused on constructing a methodology for economic evaluation of early-stage developing processes, such as second generation ethanol, aiming to show the R&D area directions to be followed for a successful industrial implementation of the process. The systematic procedure integrates bioprocess systems engineering (PSE) and economic engineering tools to perform a “retro” tecno-economic analysis. This analysis is able to identify the main process variables that influence the economic feasibility of the process and their target values. Initially, the methodology was tested on a case study involving the production of succinic acid from sucrose by fermentation. The methodology was able to eliminate one of the variables initially considered (sucrose conversion), due to its low influence on the process feasibility. Additionally, target values were obtained for the succinic acid concentration in the fermenter as a function of the selectivity and the specific productivity (the process variables chosen). Finally, the integrated production of ethanol from sugarcane juice and bagasse (first and second generation ethanol, respectively) was assessed. The three variables with the highest effect on the economic feasibility of the process were: the biocatalyst yield, the sucrose conversion and the solid mass fraction, both in the hydrolysis reactor. The reactor productivity, on the other hand, had little impact on the process feasibility. Besides, the experimental results already achieved the values needed for this variable. In general, the methodology was able to yield important information about both case studies required improvements for achieving economic feasibility. Although used in biochemical processes, the methodology is general, applying to all types of chemical processes.